Geochemistry of the lunar highlands as revealed by measurements of thermal neutrons. Issue 3 (23rd March 2016) - Peplowski, Patrick N.; Beck, Andrew W.; Lawrence, David J.
Abstract: Thermal neutron emissions from the lunar surface provide a direct measure of bulk elemental composition that can be used to constrain the chemical properties of near‐surface (depth <1 m) lunar materials. We present a new calibration of the Lunar Prospector thermal neutron map, providing a direct link between measured count rates and bulk elemental composition. The data are used to examine the chemical and mineralogical composition of the lunar surface, with an emphasis on constraining the plagioclase concentration across the highlands. We observe that the regions of lowest neutron absorption, which correspond to estimated plagioclase concentrations of >85%, are generally associated with large impact basins and are colocated with clusters of nearly pure plagioclase identified with spectral reflectance data. Key Points: We report the first map of macroscopic neutron absorption for the lunar surface Elemental composition and variability across the lunar highlands is discussed Large (>45 km diameter) locations with >85 wt % plagioclase content are identified